Future Democracies - Laboratory of Collective Intelligence for Partici patory Democracy (MediaLab Prado, 2019)
The Laboratory of Collective Intelligence for Participatory Democracy (2016-2019) is a project that arose out of Medialab Prado in coordinat ion with the Government Area of Citizen Participation, Transparency an d Open Government of the city of Madrid. Its work has been very connec ted with the analysis, reflection and innovation found on the digital participation platform Decide Madrid. The project has also organised m any workshops and conferences that have brought together hundreds of p eople from the world of participatory democracy. This publication summ arises the project’s core working principles as well as the open activ ities it has hosted over the course of these three years. These pilot experiences offer a possible vision of the future of democratic govern ance.
Keywords: Democracy